Protective effect of Glechoma hederacea extract against gallstone formation in rodent models - Min Xiao; Mengbi Yang; Xiaoyu Ji; Dan Li; Yuning Xie; Yuanfeng Lyu; Zhong Zuo (BMC, 2021)
Abstract Background Our current study aimed to evaluate the effect of an Glechoma hederacea extract (Hitrechol®) in normal rats and gallstone diseased mice to explore its underlying mechanisms. Normal rats and C57BL/6 mice with/without cholesterol gallstone were used in this study. Methods To monitor the effect of Hitrechol® on bile secretion, bile flow rates at 15 min interval until 2 h post-dosing in normal rats treated with vehicle and Hitrechol® were compared using multiple t-test with a p < 0.05 considered as statistically significant different. To further evaluate the effect of Hitrechol® against the development of gallstone in lithogenic diet treated mice, mice were treated with vehicle or Hitrechol® (QD-once daily or TID-three times daily) for 3 weeks followed by comparing the levels of bile composition among the treatment groups. In addition, the anti-oxidative biomarkers in liver and anti-inflammatory biomarkers in serum were detected and compared among all the treatment groups to evaluate the hepato-protective effect of Hitrechol®. The obtained levels of biomarkers and bile composition were compared among different treatment groups using one-way ANOVA tests followed by Tukey's multiple comparisons with p < 0.05 considered as statistically significant. Results Despite no significant impact on the bile flow rate, Hitrechol® TID treatment dramatically decreased size and amount of gallstone crystals and total cholesterol level (p < 0.05), as well as total bile acid (p < 0.05) and several types of bile acid (p < 0.05) levels in gallstone disease model mice. Hitrechol® TID treatment could significantly decrease the frequencies of hepatocyte necrosis and lipid aggregation notably as well as increase the antioxidant enzyme level (p < 0.05) in the liver. Conclusions Our findings for the first time demonstrated the beneficial effect of Hitrechol® against gallstone via its litholytic, liver-protective and antioxidant activities.